2014
DOI: 10.1105/tpc.114.123455
|View full text |Cite
|
Sign up to set email alerts
|

The Os-AKT1 Channel Is Critical for K+ Uptake in Rice Roots and Is Modulated by the Rice CBL1-CIPK23 Complex

Abstract: Potassium (K + ) is one of the essential nutrient elements for plant growth and development. Plants absorb K + ions from the environment via root cell K + channels and/or transporters. In this study, the Shaker K + channel Os-AKT1 was characterized for its function in K + uptake in rice (Oryza sativa) roots, and its regulation by Os-CBL1 (Calcineurin B-Like protein1) and Os-CIPK23 (CBL-Interacting Protein Kinase23) was investigated. As an inward K + channel, Os-AKT1 could carry out K + uptake and rescue the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
230
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 245 publications
(262 citation statements)
references
References 56 publications
11
230
0
1
Order By: Relevance
“…5). Importantly, activation of the rice (Oryza sativa) OsAKT1 (Li et al, 2014) or the grapevine (Vitis vinifera) VvK1.1 channels (Cuéllar et al, 2010) by CIPK23/CBL1 has also been described. Thus, the important regulatory role on HAK5-and AKT1-mediated K + uptake shown here for the Arabidopsis CIPK23/CBL complex can be extended to other plant species and, most importantly, to crops.…”
Section: Discussionmentioning
confidence: 99%
“…5). Importantly, activation of the rice (Oryza sativa) OsAKT1 (Li et al, 2014) or the grapevine (Vitis vinifera) VvK1.1 channels (Cuéllar et al, 2010) by CIPK23/CBL1 has also been described. Thus, the important regulatory role on HAK5-and AKT1-mediated K + uptake shown here for the Arabidopsis CIPK23/CBL complex can be extended to other plant species and, most importantly, to crops.…”
Section: Discussionmentioning
confidence: 99%
“…S11). Previous electrophysiological analyses suggested that AtKC1 function in rice is weak (Fuchs et al, 2005;Li et al, 2014), although two putative AtKC1 homologs have been found in the rice genome (Supplemental Fig. S11).…”
Section: Discussion Physiological Function Of Atkc1 In Plant Cellsmentioning
confidence: 99%
“…This CBL1/ 9-CIPK23-AKT1 pathway is an important mechanism in the Arabidopsis response to LK stress. A similar mechanism was also identified in other plant species (for review, see Véry et al, 2014), such as rice (Oryza sativa; Li et al, 2014). Subsequently, a 2C-type protein phosphatase, AIP1, was identified that interacts with and inactivates the AKT1 channel (Lee et al, 2007).…”
mentioning
confidence: 90%
“…The slope for each K + concentration was calculated according to the linear regression of the growth curves during the logarithmic growth phase. The curve was obtained by applying nonlinear regression analysis using the MichaelisMenten equation (Horie et al 2011;Li et al 2014). …”
Section: Yeast Complementation Assaysmentioning
confidence: 99%